Three birds with one stone: a disintegrable fertilizer with rapid fertilization, controlled-loss and detoxification - Xianghai Kong; Chen Sun; Ziyu You; Wanji Zhu; Xinxin Zhai; Yuhao Wang; Yan Wang; Weijian Zhang; Kaimin Zhu; Xiaoshuang Han; Pan Zhao; Yanping Zhu; et al. (Desalination, 2026)

Study on dynamic response and damage mechanism of tunnel across reverse fault based on different earthquake action modes - Rui Sun; Xiaojun Li; Yanping Yang; Ren Deng; Teng Li; Dingding Xiong (Tunnelling and Underground Space Technology, 2026)

Plasma technology regulated In3S4 nanosheets surface cationic defects enhanced photocatalytic H2O2 production in pure water - Fei Li; Yang Zhang; Yongjie Zhou; Yanping Gao; Longkai Pan; Chen Sun; Hequn Yang; Fei Rao; Gangqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Effects of stir-fried Hemp (Cannabis sativa L.) seed polysaccharides on blood deficiency syndrome in rats based on metabolomics and gut microbiota. - Minghao Sun; Haipeng Tang; Chenxi Bai; Qian Wang; Meng Liu; Yanping Sun; Qiuhong Wang; Haixue Kuang (Food Research International, 2026)

An integrated experimental and computational study on a COX-2-targeted AIE probe for precise cancer cell imaging via restriction of intramolecular rotation - Jianxi Liu; Shengfa Song; Yonglin Zhang; Jiale Hu; Shulin Chen; Lulu Zhu; Li Shen; Zhen Sun; Ying Xue; Hao Jiang; Wei Ji; Jinmei Sun; et al. (Analytica Chimica Acta, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Pomelo polysaccharides: A review of the extraction techniques, purification, structural characteristics, interactions, biological activities, applications and future prospects - Jingwei Wang; Ting Yang; Kaiyang Liu; Yuesong Xiao; Xiaoming Wang; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2026)

Enhancement of microbial protein production via hydrogen oxidizing bacteria in microbial electrolytic protein-production cell system - Rui Dong; Hangyu Sun; Yilin Jiang; Haotian Liu; Yue Wang; Xingjia Fu; Yanping Liu; Ziyi Yang (Journal of Environmental Chemical Engineering, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Microgranular activated carbon–enhanced PHA storage and PHA-driven endogenous denitrification in long-SRT activated sludge systems - Yufeng Zhang; Quan Yuan; Jinyu Hao; Yanping Zhang; Yingxue Sun (Journal of Water Process Engineering, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Harnessing molecularly imprinted polymers for multiplex detection of emerging contaminants in foods: advances and future perspectives - Quanbin Fu; Yanping Pei; Wenming Liu; Xin Sun; Peng Wu; Houshen Li; Shiyun Ai (Critical Reviews in Food Science and Nutrition, 2026)

Study on multiscale particle motion characteristics in hydraulic lifting pipe under pulsating flow conditions - Desheng Chen; Geng Li; Wenhao Sun; Yuanming Ding; Zhe Lin; Yanping Wang (Ocean Engineering, 2026)

AutoML democratizes water quality forecasting: Lowering expertise barriers - Yangyang Chu; Yun Fang; Liangzhi Sun; Yang Zhang; Liujian Wang; XiaoMeng Han; Mou Lv; Haixing Liu; Kunlun Xin; Weigang Wang; Yanping Zhu; Shihu Shu (Journal of Water Process Engineering, 2026)

Strain-specific impacts of Pichia kudriavzevii on metabolite profiles and microbial community dynamics in Chinese Baijiu fermentation: Integrated metabolomics and metagenomics analysis - Boqin Zhang; Mengbo Wang; Jia Zheng; Chenxi Yu; Chunhui Wei; Junyu Ren; Shouying Sun; Guoming Wang; Jinhua Wang; Yanping Lu; Liangcai Lin; Cuiying Zhang (International Journal of Food Microbiology, 2026)

Isolation, characterization, and application of Hanseniaspora uvarum X12 for modulating the flavor and quality of greengage wine through multi-omics and sensory analysis - Hairui Sun; Jiuhong Du; Yanping Wu; Kai Zhong; Yue Xiao; Yina Huang; Hong Gao (Food Bioscience, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Mitigating intrinsic defects and optimizing interfacial energetics via aluminum-doping toward 13.6% efficiency kesterite solar cells - Xinyu Zhang; Jingyi Meng; Zhenyan He; Chun Guo; Linxin Gao; Yanping Song; Wenjie Zhu; Sisi Jia; Busen Zhai; Lunkan Shen; Dipeng Xu; Huanhuan Sun; et al. (Chemical Engineering Journal, 2026)

Integrated morphological, transcriptomic, and metabolomic profiling reveals differential development mechanisms in two weeping forsythia genotypes during tissue culture - Yanxia He; Yanping Zheng; Jiaqi Geng; Yue Wang; Na Qi; Xu Lu; Xiaoxiao Wang; Yongjin Sun; Helong Wen; Xiaoya Liu; Xin Sun; Xianping Wang; et al. (Physiology and Molecular Biology of Plants, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

Local macrophage dynamics–inspired engineering of time-programmed nano-vaccine scaffold for postoperative cancer immunotherapy - Zhenyu Xu; Qian Chen; Mingyu Hao; Yiyang Cao; Xiaoqin Kuang; Chunjiayu Li; Zhihao Liu; Jiawen Xue; Jianing Zhao; Mengwei Zhao; Naicong Cai; Yiqing Li; et al. (Science Bulletin, 2026)

Identification and validating native biocontrol bacteria Bacillus strain MZ3-12 against bacterial wilt - Xiao Zhou; Yue Qing; Yanping Wang; Haibin Deng; Jun Wang; Mi Kuang; Xuefeng Luo; Chenran Zhao; Zheng Sun; Ye Wang; Liang Yang; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Divergent responses of maize and soybean to intercropping: Insights from arbuscular mycorrhizal fungi diversity, colonization, and related-genes expression - Shihui Yu; Xinru Liu; Ling Liu; Yanping Ma; Baohong Liu; Wuyan Xiang; Ying Zhang; Peiyong Liu; Chen Feng; Caixia Sun (Plant and Soil, 2026)

High-resolution skin-like microlithographic displays for visual-tactile system - Baoying Sun; Xiaoli Zhao; Chuang Xue; Mingxin Zhang; Pengbo Xi; Guoqiang Ren; Hao Liu; Junru Zhang; Yanping Ni; Yanhong Tong; Liangwen Feng; Qingxin Tang; et al. (Chemical Engineering Journal, 2026)

An R2R3-MYB transcription factor TgMYB44 positively regulates petal senescence by enhancing ABA biosynthesis in tulip - Haipo Yang; Yikun Wu; Chengxiao Yuan; Hongqing Yin; Lin Xiang; Xuewei Wu; Honglin Deng; Bo Sun; Zhulong Chan; Yanping Wang (Plant Cell Reports, 2026)

Fungal communities dominate accumulation of microbial necromass carbon after 11-year revegetation in a semi-arid desert mining area - Pengfei Li; Wenjiang Fu; Yiwei Bai; Daren Zhou; Shiqi Sun; Qiao Guo; Jianguo Zhang; YanPing Miao; Hangxian Lai (Journal of Environmental Management, 2026)

Unvegetated Tidal Flats: A Critical Yet Vulnerable Coastal Blue Carbon Sink - Yanping Wang; Changchun Li; Zhaoliang Peng; Jing Luo; Senlin Zhu; Yumeng Sun; Ruping Liu; Dongcheng Jiang; Xiangqian Zhou; Faming Wang (Global Change Biology, 2026)
Unvegetated tidal flats, despite accounting for approximately 24.9% of global blue carbon ecosystem area, remain underrepresented in blue carbon budgets. Here, we synthesize data from 184 sites across 23 countries to quantify their carbon stocks, carbon accumulation rate (CAR) and greenhouse gas (GHG, CO 2 and CH 4 ) emissions. Our results reveal that tidal flats sequester 8.6 (4.5–9.9) Tg C yr −1 and store 1.2 (0.7–2.0) Pg C in the top meter of sediments, increasing global blue carbon estimates by 6%–17%. However, they simultaneously emit 0.073 Tg CH 4 yr −1 (3.3 Tg CO 2 eq yr −1 ), 27.9% of the CH 4 emissions from salt marshes, offsetting 14.1% (1.8%–20.4%) of their carbon sequestration benefits. Mudflats exhibit the highest carbon stocks and CO 2 fluxes among different sediment types, primarily due to their abundant binding sites of fine‐grained particles and stronger microbial activities. Both CAR and CH 4 fluxes decline poleward, with tropical zone as hotspots. Our findings highlight the urgency of integrating tidal flats into climate mitigation strategies, particularly given their vulnerability to land‐use changes and sea‐level rise. Conservation efforts must balance carbon sequestration gains against CH 4 trade‐offs to optimize their climate regulation potential.

A new method of consistency evaluation of brain drugs: a case study of edaravone - Liqiang Gu; Yanping Hu; Yinfang Lai; Sheng Zhang; Haoran Wang; Xiaozhen Xu; Lingfang Chen; Yuhua Shi; Jiechao Chen; Xiaochun Sun; Yuan Zhang; Lingzhi Hu (Regulatory Toxicology and Pharmacology, 2025)

Superior energy storage and charge-discharge performance achieved in (Pb1-3/2La )(Hf0.9Sn0.1)O3 antiferroelectric ceramics - Shuifeng Li; Xiaobin Guo; Zhenhua Tang; Xin-gui Tang; Qijun Sun; Yanping Jiang; Wenhua Li; Qiuxiang Liu (Chemical Engineering Journal, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Selenium-Enriched Lactiplantibacillus plantarum ZZU 8–12 Regulates Intestinal Microbiota and Inhibits Acute Liver Injury - Yanping Wang; Hengyu Ma; Haolong Li; Yuhang Huang; Yupeng Tang; Xiaoxue Tang; Pintian Sun; Zhongfang Tan; Huili Pang; Fengyuan Yang (Probiotics and Antimicrobial Proteins, 2025)

Erratum to: Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

Polysaccharides from Actinidia Lindl.: Extraction, bioactivities, and emerging applications in food and pharmaceutical industries - Lihao Wang; Chenqing Dong; Qian Wang; Chi Teng; Wuyou Gao; Yujia He; Jun Liang; Yonggang Xia; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2025)

Analysis of human electroencephalogram features in hypobaric oxygen-enriched environments - Mingxi Yang; Xuanyuan Gou; Liangliang Sun; Xiaowen Su; Yanping Yuan (Building and Environment, 2025)

MSSI: a multi-scale shift-invariant metric learning network for visible and long-wave infrared image patch matching - Xiuwei Zhang; Yanping Li; Zhaoshuai Qi; Yue Liang; Yi Sun (International Journal of Remote Sensing, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Synergistic bulk and back interface passivation enabled by in situ Ag-doping and Nb-engineering for efficient kesterite solar cells - Wenjie Zhu; Sisi Jia; Jingyi Meng; Chun Guo; Xinyu Zhang; Linxin Gao; Yixiang Xiao; Yanping Song; Jiayong Zhang; Huanhuan Sun; Jin Wang; Shihua Huang; et al. (Chemical Engineering Journal, 2025)

Rapid Post-Earthquake Impact and Recovery Assessment: The 2025 Mw 7.7 Myanmar Earthquake - Wenkai Chen; Jiajie Wu; Gang Rao; Xue Li; Lize Chen; Yuyang Peng; Zhenhang Zhang; Ming Yi; Yanping Sun (Journal of Earth Science, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Solvation–interface coupling strategy enables dendrite-free zinc anodes via amino acid-derived poly(ionic liquid) films - Kexuan Zang; Wenqi Song; YanPing Sun; Puang Lu; Sufeng Zhang; Zongchen Miao; Liwei Qian; Valentin Nica; Mohaned Hammad (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

A novel method of calculating mean skin temperature with high thermal sensitivity for thermal sensation evaluation - Xiaowen Su; Ongun Berk Kazanci; Bjarne W. Olesen; Liangliang Sun; Yanping Yuan (Energy and Buildings, 2025)

Synthesizing ZIF-8 functionalized biochar by in situ reuse of residual Zn from chemical activation for enhanced tetracycline hydrochloride adsorption removal - Jianying Liu; Qian Zeng; Yao Chen; Zhongde Dai; Wenju Jiang; Lu Yao; Junfeng Zheng; Dengrong Sun; Yanping Wu; Lin Yang (Journal of Environmental Chemical Engineering, 2025)

Redox-active ligands for oxygen evolution reactions activity: Modulation of metal valence states in synthesis and accelerated reconstruction by rapid hydrolysis in alkaline electrolytes - Pengxin Sun; Jing Liu; Li Wang; Cheng Wu; Ronghua Jiang; Jun Huang; Yanping Hou; Mingjie Li; Boge Zhang; Zebin Yu (Journal of Environmental Chemical Engineering, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

Interpretation of the Budyko framework for monthly evapotranspiration prediction of individual basins - Hao Sun; Xingwang Wang; Yanping Qu; Juan Lyu; Hehe Cai; Xuejun Zhang (Atmospheric Research, 2025)

Effects of simulated microgravity on dental pulp stem cell stemness - Huailong Hou; Zhengjun Qiu; Jingyi Che; Yanping Li; Jingxuan Sun; Weiwei Zhang; Jinjie Ma; Shuang Zhang; Mengdi Li; Yumei Niu; Lina He (Journal of Molecular Histology, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Assessing the feasibility of adjusting the dry matter content utilizing corn grits and cottonseed meal and inoculating with Lactiplantibacillus plantarum in the production of fermented feed from kitchen waste - Yupeng Tang; Fengyuan Yang; Huili Pang; Shanshan Zhao; Hengyu Ma; Haolong Li; Yuhang Huang; Pintian Sun; Xiaoxue Tang; Yanping Wang (Process Safety and Environmental Protection, 2024)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Characteristics of volatile organic compounds under different operating conditions in a petrochemical industrial zone and their effects on ozone formation - Yanping Yang; Xianhong Meng; Qiang Chen; Qiang Xue; Lina Wang; Jian Sun; Wenkai Guo; Huijie Tao; Lili Yang; Feifei Chen (Environmental Pollution, 2024)

Effects of hypobaric hypoxia on human physiological and psychological responses in hot-humid environments - Yue Hu; Liangliang Sun; Guorong Xu; Xiaowen Su; Yanping Yuan (Building and Environment, 2024)

Field experiment on transient thermal comfort in a Chinese railway station – High temperature exposures - Xiaowen Su; Wei Liu; Richard de Dear; Liangliang Sun; Yanping Yuan (Building and Environment, 2024)

Experimental investigation on strength characteristics of marine soft clay under monotonic and cyclic loading - Lin Guo; Hao Wu; Yanping He; Hui Li; Yilong Sun (Marine Georesources & Geotechnology, 2024)

Auxin Receptor TRANSPORT INHIBITOR RESPONSE1 Promotes Tulip Plant Growth and Bulb Swelling - Qi Sun; Bei Zhang; Lin Xiang; Yanping Wang; Zhulong Chan (Journal of Plant Growth Regulation, 2024)

A prediction method for favorable hydrocarbon accumulation areas in carbonate oil reservoirs based on machine learning and driven by formation water chemical characteristic data - Zhiwei Chen; Jianbo Gao; Hong Pang; Zhipeng Huo; Ningliang Sun; Yanping Lv; Yan Wang; Bo Wu (Carbonates and Evaporites, 2024)

Numerical investigation on effects of fuel rod with the position of bow deformation on the flow and heat transfer of PWR - Chengde Li; Mei Huang; Delong Sun; Xiaoping Ouyang; Yanping Huang; Yang Liu (Annals of Nuclear Energy, 2024)

Evaluating AGS efficiency in PHA synthesis and extraction integrated with nutrient removal: The impact of COD concentrations - Quan Yuan; Song Chen; Yun Chen; Xinyu Zhang; Yuqing Lou; Xueting Li; Qian Liang; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

Removal of calcium from phosphoric acid produced by the nitric acid process using solvent extraction with TCHDGA and stripping with water - Chengjin Xu; Miaomiao Zhang; Jianhui Su; Xiujing Peng; Xiangfeng Kong; Yanping Luo; Jiahui Sun; Yu Cui; Xuchuan Jiang; Guoxin Sun (Hydrometallurgy, 2024)

PhERF71 regulates petunia flower senescence by modulating ethylene biosynthesis - Xiaotong Ji; Yanxiang Mao; Yanping Yuan; Meiling Wang; Yike Zhao; Lei Zhang; Daoyang Sun (Postharvest Biology and Technology, 2024)

Source apportionment of organic carbon and nitrogen in sediments from river and lake in the highly urbanized Changjiang Delta - Yalong Li; Yaojen Tu; Tingting Sun; Yanping Duan; Jiayi Kou; Weikun Li; Jiaxin Gao (Journal of Hazardous Materials, 2024)

Upcycling of nutrients from kitchen waste: Integration of anaerobic digestion system and microbial protein production system - Qile Zhu; Kangjian Gao; Qi Sun; Chuan Ma; Yuxing Luo; Zijin Niu; Yanping Liu; Ziyi Yang (Journal of Environmental Management, 2024)

Cellular Senescence-Related Long Non-coding RNA Signatures Predict Prognosis in Juvenile Osteosarcoma - Peng Zhao; Junli Chang; YeKai Chen; Xingyuan Sun; Xiaoping Ma; Chujie Zhou; Lei Zhou; Yongjun Wang; Yanping Yang (Phenomics, 2024)
Osteosarcoma is the most common malignant bone tumor and is frequently diagnosed in juvenile. Cellular senescence is a fundamental hallmark of osteosarcoma and plays a vital role in the initiation and progression of aging and tumorigenesis. Long non-coding RNAs (lncRNAs) are implicated in tumorigenesis. In this study, six cellular senescence-related lncRNAs with independent prognostic significance in juvenile osteosarcoma patients were identified through univariate Cox regression analysis, least absolute shrinkage and selection operator (LASSO) regression analysis, and multivariate Cox regression analysis. Prognostic significance was further confirmed by Kaplan–Meier (KM) survival curves, co-expression interaction networks, and sankey diagrams. A prognostic model of cellular senescence-related genes in juvenile osteosarcoma patients was then constructed using multivariate Cox regression analysis based on these six genes. High- and low-risk groups were identified according to the median risk score calculated by the prognostic model. The favorable prognostic significance of this model was demonstrated through survival curves, receiver operating characteristic (ROC) curves, distribution scatter plots and lncRNA expression heatmaps. Furthermore, cellular senescence-related lncRNAs were validated by enrichment analysis, immunological correlation analysis, m 6 A correlation analysis, and drug sensitivity correlation analysis. These findings are important for improving the prognosis of juvenile osteosarcoma patients and understanding the mechanisms underlying cellular senescence in juvenile osteosarcoma development.

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Design of Auto-Adaptive Drug Delivery System for Effective Delivery of Peptide Drugs to Overcoming Mucus and Epithelial Barriers - Ruihuan Ding; Yanping Li; Wei Zheng; Yiying Sun; Zhenyu Zhao; Houqian Zhang; Ranran Yuan; Aiping Wang; Kaoxiang Sun; Hongbo Wang; Yanan Shi (The AAPS Journal, 2024)

Effect of long-term dosage of hydrazine on mainstream anammox process: Biofilm characteristics and microbial community - Quan Yuan; Yuqing Lou; Song Chen; Yun Chen; Xueting Li; Xinyu Zhang; Liang Qian; Yanping Zhang; Yingxue Sun (Chemosphere, 2024)

The applicability of a SIF-based mechanistic model for estimating GPP at the canopy scale - Yanping Liu; Zhaoyong Hu; Genxu Wang; Arthur Gessler; Shouqin Sun (Agricultural and Forest Meteorology, 2024)

Enhanced ofloxacin degradation in water by a novel integrated photocatalysis and rotating magnetic field system - Ning Ding; Sijia Zhang; Jianxin Zhang; Yang Zhan; Bokang Wang; Hong Liu; Yanping Zhang; Yingxue Sun (Journal of Water Process Engineering, 2024)

Research on leaching behavior of manganese and ammonia nitrogen in electrolytic manganese residue under oxalic acid/hydrogen peroxide system - Chenxin Sun; Yu Zhang; Yanping Yang; Qian Shang; Yunqiu Liu; Qianlin Chen (Journal of Water Process Engineering, 2024)

Influence of organic sulfur gas-phase sulfation on the NH3-SCR activity of CeO2 catalyst: The competitive adsorption and conversion of CS2 and COS at a low hydrolysis temperature - Zhibo Xiong; Zhenchang Sun; Jiaxing Liu; Yanping Du; Yafei Zhu; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Fuel, 2024)

The feeding strategies of the antarctic lanternfish electrona antarctica (pisces: myctophidae) in the amundsen and cosmonaut seas (southern ocean), assessed with a classification tree analysis - Mi Duan; Chi Zhang; Yanping Luo; Libao Gao; Guankui Liu; Chunlin Liu; Yongming Sun; Jianchao Li; Shuyang Ma; Wenchao Zhang; Yongjun Tian (Polar Biology, 2024)

Genome-wide identification of nitrate transporter 1/peptide transporter family (NPF) induced by arbuscular mycorrhiza in the maize genome - Qiang Xu; Yanping Wang; Wen Sun; Yuanhao Li; Yunjian Xu; Beijiu Cheng; Xiaoyu Li (Physiology and Molecular Biology of Plants, 2024)

SlCNR regulates postharvest water loss and wax accumulation in tomato fruit and directly represses the transcription of very-long-chain (VLC) alkane biosynthesis-related genes SlCER1-2 and SlCER6 - Di Chen; Tingyu Wang; Hua Huang; Qiaoli Zhang; Xue Chen; Zongyan Sun; Yanping Song; Yuetong Yi; Chengxia Liu; Donald Grierson; Jiankang Cao; Daqi Fu; et al. (Postharvest Biology and Technology, 2024)

Pretreatment greatly facilitates ethyl levulinate production from catalytic alcoholysis of Napier grass stem - Huai Liu; Yanping Kong; Weipeng Song; Rui Zhang; Junhua Zhang; Yong Sun; Lincai Peng (Chemical Engineering Journal, 2024)

Thermal performance of a solar heat collection and storage wall with night insulation in winter: A numerical study - Yafen Sun; Nan Zhang; Zhaoli Zhang; Muhammad Sultan; Yanping Yuan (Energy and Buildings, 2024)

Improving food security and farmland carbon sequestration in China through enhanced rock weathering: Field evidence and potential assessment in different humid regions - Fuxing Guo; Haowei Sun; Jing Yang; Linsen Zhang; Yan Mu; Yanping Wang; Fuyong Wu (Science of The Total Environment, 2023)

Promotional effect of H2O introduction on the NH3-SCR activity of the gas-phase sulfated CeO2 catalyst by organic CS2+COS: Influence of H2O concentration - Jiaxing Liu; Yafei Zhu; Zhenchang Sun; Yanping Du; Zhibo Xiong; Fei Zhou; Jing Jin; Qiguo Yang; Wei Lu (Journal of Environmental Chemical Engineering, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Effective degradation of tetracycline by Pd/AG/ITO electrode: Electrode preparation, characterization, kinetics, degradation mechanism and toxicity assessment - Chen Shao; Jian Zhang; Yuqing Liu; Yuting Jiang; Yanping Jia; Guomin Li; Zhong Sun (Journal of Environmental Chemical Engineering, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

Detoxification and resource utilization of soda ash chromite ore processing residue by copper slag - Lanbin Wang; Yangming Xu; Yanping Ma; Yu Chen; Anju Yang; Guixiang Gan; Yaguang Du; Yan Sun (Process Safety and Environmental Protection, 2023)

Corn-straw-derived, pyridine-nitrogen-rich NCQDs modified Cu0.05Zn2.95In2S6 promoted directional electrons transfer and boosted adsorption and activation of CO2 for efficient photocatalytic reduction of CO2 to CO - Jinhang Yang; Yanping Hou; Jiangli Sun; Jingwen Wei; Shiming Zhang; Jiaxiang Liang; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Exploring the diagnostic value, prognostic value, and biological functions of NPC gene family members in hepatocellular carcinoma based on a multi-omics analysis - Keheng Chen; Xin Zhang; Huixin Peng; Fengdie Huang; Guangyu Sun; Qijiang Xu; Lusheng Liao; Zhiyong Xing; Yanping Zhong; Zhichao Fang; Meihua Liao; Shihua Luo; et al. (Functional & Integrative Genomics, 2023)

Bridging the gap between artificial intelligence and mental health - Tangsheng Lu; Xiaoxing Liu; Jie Sun; Yanping Bao; Björn W. Schuller; Ying Han; Lin Lu (Science Bulletin, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Crop productivity and soil inorganic carbon change mediated by enhanced rock weathering in farmland: A comparative field analysis of multi-agroclimatic regions in central China - Fuxing Guo; Yanping Wang; Haoyong Zhu; Chuangye Zhang; Haowei Sun; Zhuling Fang; Jing Yang; Linsen Zhang; Yan Mu; Yu Bon Man; Fuyong Wu (Agricultural Systems, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

Kinetics and mechanisms of bacteria disinfection by performic acid in wastewater: In comparison with peracetic acid and sodium hypochlorite - Ning Ding; Ziwei Li; Lin Jiang; Hong Liu; Yanping Zhang; Yingxue Sun (Science of The Total Environment, 2023)

Electron-buffer-mediated dual Z-scheme ZnSe/Ag2Se/AgBr heterojunction for efficient CO2 photocatalytic reduction - Ting Liang; Jingwen Wei; Shiming Zhang; Jinhang Yang; Jiangli Sun; Zuji Li; Zhihong Li; Zebin Yu; Shuangfei Wang; Yanping Hou (Journal of Environmental Chemical Engineering, 2023)

Widely targeted metabolomic approach reveals dynamic changes in non-volatile and volatile metabolites of peanuts during roasting - Dong Zhang; Dongyu Shen; Yanping Cao; Xiaoliang Duan; Hui Sun (Food Chemistry, 2023)

A double-glazed solar air-phase change material collector for nocturnal heating: Model development and sensitivity analysis - Li Yang; Nan Zhang; Yanping Yuan; Fariborz Haghighat; Mohamed Dardir; Karthik Panchabikesan; Qinrong Sun (Energy and Buildings, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

Nitrogen doping excited Ru and Ti3C2−xNx support for hydrogen generation from ammonia borane - Licheng Liang; Linyan Bian; Yanping Fan; Shuyan Guan; Xianyun Liu; Qunying Sun; Baozhong Liu (Fuel, 2023)

Local thermal comfort chart for non-uniform building environments: Comparison with vehicle environments and its application - Xiaowen Su; Ongun Berk Kazanci; Zhaojun Wang; Bjarne W. Olesen; Liangliang Sun; Yanping Yuan (Building and Environment, 2023)

Multi-color solid-state photoluminescence from orthogonally multi-stimuli-responsive organic molecule for advanced information storage and encryption - Qi Zhang; Li Yang; Yanfei Gao; Yanping Xiang; Hongjuan Li; Shiguo Sun; Yongqian Xu (Chemical Engineering Journal, 2023)

The development and future frontiers of global ecological restoration projects in the twenty-first century: a systematic review based on scientometrics - Xue Jiang; Yitao Sun; Yanping Qu; Houyuan Zeng; Jingtian Yang; Kaiyou Zhang; Lei Liu (Environmental Science and Pollution Research, 2023)

Characteristics of volatile organic compounds and secondary organic aerosol pollution in different functional areas of petrochemical industrial cities in Northwest China - Yanping Yang; Wenkai Guo; Jian Sun; Qiang Chen; Xianhong Meng; Lina Wang; Huijie Tao; Lili Yang (Science of The Total Environment, 2023)

MnOx@N-doped carbon nanosheets derived from Mn-MOFs and g-C3N4 for peroxymonosulfate activation: Electron-rich Mn center induced by N doping - Yue Zhao; Xiaohui Zhan; Yanping Sun; He Wang; Lei Chen; Junyan Liu; Huixiang Shi (Chemosphere, 2023)

PlZFP mediates the combinatorial interactions of abscisic acid with gibberellin and ethylene during flower senescence in cut herbaceous peony - Xiaotong Ji; Yanping Yuan; Zhangzhen Bai; Meiling Wang; Lixin Niu; Daoyang Sun (Postharvest Biology and Technology, 2023)

Sinusoidal stretchable fibrous electrodes regulate cardiac contraction - Yanping Zhang; Alice Le Friec; Di Sun; Menglin Chen (Chemical Engineering Journal, 2023)

Cu doping and Ti3C2OH quantum dots co-modifications of Zn3In2S6 boosted photocatalytic reduction of CO2 to CO via accelerating carriers transfer and enhancing CO2 adsorption and activation - Jinhang Yang; Yanping Hou; Jiangli Sun; Ting Liang; Tingting Zhu; Jiaxiang Liang; Xiaoqiong Lu; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Chemical Engineering Journal, 2023)

Untargeted Metabolomic Analysis Reveals the Metabolic Disturbances and Exacerbation of Oxidative Stress in the Cerebral Cortex of a BTBR Mouse Model of Autism - Can Cao; Qi Li; Yanping Chen; Mingyang Zou; Caihong Sun; Xiangning Li; Lijie Wu (Journal of Molecular Neuroscience, 2023)

Dynamic agricultural drought risk assessment for maize using weather generator and APSIM crop models - Yaxu Wang; Juan Lv; Hongquan Sun; Huiqiang Zuo; Hui Gao; Yanping Qu; Zhicheng Su; Xiaojing Yang; Jianming Yin (Natural Hazards, 2022)

Polyethylene microplastic exposure and concurrent effect with Aeromonas hydrophila infection on zebrafish - Ning Ding; Lin Jiang; Xiao Wang; Chun Wang; Yue Geng; Jianxin Zhang; Yingxue Sun; Yanping Zhang; Quan Yuan; Hong Liu (Environmental Science and Pollution Research, 2022)

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

X-ray Irradiation Improves Neurological Function Recovery of Injured Spinal Cord by Inhibiting Inflammation and Glial Scar Formation - Yi Wang; Yanping Niu; Fanguo Lin; Peng Su; Liesong Chen; Dong Liu; Yongming Sun (Journal of Molecular Neuroscience, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Synchronous removal of tetracycline and copper (II) over Z‑scheme BiVO4/rGO/g-C3N4 photocatalyst under visible-light irradiation - Jiangli Sun; Yiyuan Rong; Yanping Hou; Lingli Tu; Qingyu Wang; Yuying Mo; Shuxuan Zheng; Zan Li; Zuji Li; Zebin Yu (Environmental Science and Pollution Research, 2022)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Genetic dynamics of earlier maturity group emergence in south-to-north extension of Northeast China soybeans - Mengmeng Fu; Yanping Wang; Haixiang Ren; Weiguang Du; Deliang Wang; Rongjun Bao; Xingyong Yang; Zhongyan Tian; Lianshun Fu; Yanxi Cheng; Jiangshun Su; Bincheng Sun; et al. (Theoretical and Applied Genetics, 2020)

New Insights on ‘GALA’ Apple Fruit Development: Sugar and Acid Accumulation: A Transcriptomic Approach - Hongxia Tao; Hanqing Sun; Yufei Wang; Xuena Song; Yanping Guo (Journal of Plant Growth Regulation, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Beraprost sodium mitigates renal interstitial fibrosis through repairing renal microvessels - Shulin Li; Yanping Wang; Lu Chen; Zhuojun Wang; Guodong Liu; Bangjie Zuo; Caixia Liu; Dong Sun (Journal of Molecular Medicine, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Evolution, functional differentiation, and co-expression of the RLK gene family revealed in Jilin ginseng, Panax ginseng C.A. Meyer - Yanping Lin; Kangyu Wang; Xiangyu Li; Chunyu Sun; Rui Yin; Yanfang Wang; Yi Wang; Meiping Zhang (Molecular Genetics and Genomics, 2018)

Position and Angular Misalignment Analysis for Implantable Wireless Power Transfer System Based on Magnetic Resonance - Fei-Xiang Gong; Zhiqiang Wei; Haokun Chi; Bo Yin; Ying Sun; Yanping Cong; Mingui Sun (Journal of Medical and Biological Engineering, 2017)

Tolerance and Removal Mechanisms of Heavy Metals by Fungus Pleurotus ostreatus Haas - Suqin Yang; Xiaoxue Sun; Yanping Shen; Cheng Chang; Erhui Guo; Guixiao La; Yong Zhao; Xuanzhen Li (Water, Air, & Soil Pollution, 2017)

Bmi1 Regulates the Proliferation of Cochlear Supporting Cells Via the Canonical Wnt Signaling Pathway - Xiaoling Lu; Shan Sun; Jieyu Qi; Wenyan Li; Liman Liu; Yanping Zhang; Yan Chen; Shasha Zhang; Lei Wang; Dengshun Miao; Renjie Chai; Huawei Li (Molecular Neurobiology, 2017)

Human cytomegalovirus-encoded miR-US4-1 promotes cell apoptosis and benefits discharge of infectious virus particles by targeting QARS - Yaozhong Shao; Ying Qi; Yujing Huang; Zhongyang Liu; Yanping Ma; Xin Guo; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2016)

A cluster of 3′ coterminal transcripts from US12–US17 locus of human cytomegalovirus - Ying Lu; Yanping Ma; Zhongyang Liu; Liying Han; Shuang Gao; Bo Zheng; Chang Liu; Ying Qi; Zhengrong Sun; Yujing Huang; Qiang Ruan (Virus Genes, 2016)

Particle-Associated Ambient Benzo[a]pyrene and Levels of Urinary 1-Hydroxypyrene in a Non-occupationally Exposed Population of Adults and Children in Lanzhou, China - Yunjiang Yu; Qiong Wang; Liangzhong Li; Zien Liu; Peng Sun; Yanping Zhang; Haipeng Lin; Mingdeng Xiang; Hui Li; Bigui Lin (Bulletin of Environmental Contamination and Toxicology, 2016)

Human cytomegalovirus miR-UL36-5p inhibits apoptosis via downregulation of adenine nucleotide translocator 3 in cultured cells - Xin Guo; Yujing Huang; Ying Qi; Zhongyang Liu; Yanping Ma; Yaozhong Shao; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

Transcriptome-wide analysis of dynamic variations in regulation modes of grapevine microRNAs on their target genes during grapevine development - Chen Wang; Xiangpeng Leng; Yanyi Zhang; Emrul Kayesh; Yanping Zhang; Xin Sun; Jinggui Fang (Plant Molecular Biology, 2014)

Dissipation, residues, and risk assessment of spirodiclofen in citrus - Haibin Sun; Congyun Liu; Siwei Wang; Yanping Liu; Mingjin Liu (Environmental Monitoring and Assessment, 2013)

Fruit skin color and the role of anthocyanin - Emrul Kayesh; Lingfei Shangguan; Nicholas Kibet Korir; Xin Sun; Nadira Bilkish; Yanping Zhang; Jian Han; Changnian Song; Zong-Ming Cheng; Jinggui Fang (Acta Physiologiae Plantarum, 2013)

Down-regulation of human cytomegalovirus UL138, a novel latency-associated determinant, by hcmv-miR-UL36 - Yujing Huang; Ying Qi; Yanping Ma; Rong He; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Dissipation and residue of azoxystrobin in banana under field condition - Siwei Wang; Haibin Sun; Yanping Liu (Environmental Monitoring and Assessment, 2013)

Dissipation and Residue of Spinosad in Zucchini Under Field Conditions - Yanping Liu; Haibin Sun; Siwei Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

Transcriptional Regulation of Genes Encoding Key Enzymes of Abscisic Acid Metabolism During Melon (Cucumis melo L.) Fruit Development and Ripening - Yufei Sun; Pei Chen; Chaorui Duan; Pang Tao; Yanping Wang; Kai Ji; Yin Hu; Qian Li; Shengjie Dai; Yan Wu; Hao Luo; Liang Sun; et al. (Journal of Plant Growth Regulation, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Dissipation and Residue of Myclobutanil in Lychee - Yanping Liu; Haibin Sun; Fengmao Liu; Siwei Wang (Bulletin of Environmental Contamination and Toxicology, 2012)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

CO2 mitigation potential in farmland of China by altering current organic matter amendment pattern - ZuBin Xie; Gang Liu; QiCheng Bei; HaoYe Tang; JinShan Liu; HuiFeng Sun; YanPing Xu; JianGuo Zhu; Georg Cadisch (Science China Earth Sciences, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Diagnostic value of HCMV pp65 antigen detection by FCA for symptomatic and asymptomatic infection: compared to quantification of HCMV DNA and detection of IgM antibody in infants - Zhengrong Sun; Xiangshi Ceng; Zhiqin Mao; Jidong Wang; Qing Liu; Yaohua Ji; Yanping Ma; Ying Qi; Rong He; Qiang Ruan (Medical Microbiology and Immunology, 2009)

Preparation and some properties of cholesterol oxidase from Rhodococcus sp. R14-2 - Chengtao Wang; Yanping Cao; Baoguo Sun; Baoping Ji; M. J. Robert Nout; Ji Wang; Yonghuan Zhao (World Journal of Microbiology and Biotechnology, 2008)

Human cytomegalovirus UL145 gene is highly conserved among clinical strains - Zhengrong Sun; Ying Lu; Qiang Ruan; Yaohua Ji; Rong He; Ying Qi; Yanping Ma; Yujing Huang (Journal of Biosciences, 2007)

Semi-active model predictive control for 3rd generation benchmark problem using smart dampers - Guiyun Yan; Bingnan Sun; Yanping Lü (Earthquake Engineering and Engineering Vibration, 2007)

Effective induction of immune tolerance by portal venous infusion with IL-10 gene-modified immature dendritic cells leading to prolongation of allograft survival - Ming Zhang; Quanxing Wang; Yushan Liu; Yanping Sun; Guoshan Ding; Zhiren Fu; Zhilian Min; Youhua Zhu; Xuetao Cao (Journal of Molecular Medicine, 2004)